Accuracy of Bankruptcy Prediction Models for Coal Companies in Indonesia - Rudianto, Dudi; Susilo, Tri Pujadi; Asmara, Ikhsan Yudha (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
This research aims to conduct analysis of the accuracy of predictions of company bankruptcy using 3 main models, namely the Modified Altman, Springate and Zmijewski models, empirical studies on coal companies listed on the Indonesia Stock Exchange for the 2020-2022 period. From this research it is known that from the bankruptcy prediction model used, there is 1 company that will consistently experience potential bankruptcy prediction, namely ARXX, one of the coal producers in Indonesia which has been established since 2007, which in the last 6 years has experienced very poor financial performance, because the company has debts that continue to accumulate, problematic assets caused by non-operating subsidiaries, and continues to experience negative profit balances so that the company is unable to provide dividends to its shareholders. The results show that the Zmijewsky Model is the bankruptcy prediction model with the highest level of accuracy, next is the Modified Altman Model and finally the Springate Model. Based on the results of the ANOVA test it is known that the three bankruptcy prediction models, namely the Modified Altman, the Springate and the Zmijewsky Model, have significant differences, where each model focuses on assessing bankruptcy predictions on different aspects.